if sinx +sinx+sinz=-3 , prove that cosx + cosy+cosz=0
Answers
Answered by
1
Sin x + Sin y + Sin z = -3
Sin x = Sin y = Sin z = -1
Now,
![\cos(x) = \sqrt{1 - {sin}^{2} x} = \sqrt{1 - ({ - 1})^{2} } = 0 \\ similarly \: \cos \: y \: = \cos \: z = 0 \\ \\ hence \: \: \cos(x ) + \cos(y) + \cos(z) = 0 + 0 + 0 = 0 \cos(x) = \sqrt{1 - {sin}^{2} x} = \sqrt{1 - ({ - 1})^{2} } = 0 \\ similarly \: \cos \: y \: = \cos \: z = 0 \\ \\ hence \: \: \cos(x ) + \cos(y) + \cos(z) = 0 + 0 + 0 = 0](https://tex.z-dn.net/?f=+%5Ccos%28x%29++%3D++%5Csqrt%7B1+-++%7Bsin%7D%5E%7B2%7D+x%7D++%3D++%5Csqrt%7B1+-++%28%7B+-+1%7D%29%5E%7B2%7D+%7D++%3D+0+%5C%5C+similarly++%5C%3A+%5Ccos+%5C%3A+y+%5C%3A++%3D++%5Ccos+%5C%3A+z+%3D+0+%5C%5C++%5C%5C+hence+%5C%3A++%5C%3A++%5Ccos%28x+%29+%2B++%5Ccos%28y%29++%2B++%5Ccos%28z%29+++%3D+0+%2B+0+%2B+0+%3D+0)
Sin x = Sin y = Sin z = -1
Now,
Answered by
3
Dear here is ur solution
It is given that sinx +siny+sinz=-3
We can write it as
sinx+Siny+sinz=-1-1-1
We can say that sinx=-1 &Siny=-1 &sinz=-1
So we find out value of x, y&z
so value of x, y&z=270°
We put these values in question
Cos270°+cos270°+cos270°=0
I hope it helps you
It is given that sinx +siny+sinz=-3
We can write it as
sinx+Siny+sinz=-1-1-1
We can say that sinx=-1 &Siny=-1 &sinz=-1
So we find out value of x, y&z
so value of x, y&z=270°
We put these values in question
Cos270°+cos270°+cos270°=0
I hope it helps you
Similar questions